Mechanisms of bone destruction in multiple myeloma. (21st September 2017) - Terpos, E.; Christoulas, D.; Gavriatopoulou, M.; Dimopoulos, M.A.
Abstract : Osteolytic bone disease is a frequent complication of multiple myeloma, resulting in skeletal complications that are a significant cause of morbidity and mortality. It is the result of an increased activity of osteoclasts, which is not followed by reactive bone formation by osteoblasts. Recent studies have revealed novel molecules and pathways that are implicated in osteoclast activation and osteoblast inhibition. Among them, the most important include the receptor activator of nuclear factor‐kappa B ligand/osteoprotegerin pathway, the macrophage inflammatory proteins and the activin‐A that play a crucial role in osteoclast stimulation in myeloma, while the wingless‐type (Wnt) signalling inhibitors (sclerostin and dickkopf‐1) along with the growth factor independence‐1 are considered the most important factors for the osteoblast dysfunction of myeloma patients. Finally, the role of osteocytes, which is the key cell for normal bone remodelling, has also revealed during the last years through their interaction with myeloma cells that leads to their apoptosis and the release of RANKL and sclerostin maintaining bone loss in these patients. This review focuses on the latest available data for the mechanisms of bone destruction in multiple myeloma.